Manusia Tersesat Tanpa Adanya Implementasi Komunikasi dalam Perspektif Al-Qur’an Terhadap Kondisi Kehidupan Masyarakat - Yusuf, Mochamad Aris; Fitriani, Nanda Elma (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Without communication, humans can be said to be lost in the wilderness of life because they are unable to place themselves in the social sphere, as in the case of mutilation. Communication is a very important part of human life. In the mean time, the Qur'an is the best aide for Muslims as an aide in love, or in day today existence with regards to correspondence. The Qur'an itself contains material on correct and effective communication as well as respecting others through ethical communication. By putting into practice the Islamic values of truth, the purpose of this study is to combat social crime by using individual communication. This study employs a descriptive-qualitative approach with the writer's role as the primary instrument.  The object of this research is the mutilation case carried out by Tarsum against his wife Yanti. The findings of this study support cognitive and behavioral theories, which provide an explanation for how a person's psychological characteristics compare to those of a highly dynamic group. Aside from that, there are likewise seven words that are basic to the execution of the Al-Qur'a, to be specific; qaulan sadidan, qaulan ma'rufan, qaulan balighan, qaulan masyuran, qaulan layyinan, qaulan kariman, and qaulan syawira. However, complex cases and other solutions must be investigated in order to advance this research.